Proceedings of the 2013 Conference on Internet Measurement Conference 2013
DOI: 10.1145/2504730.2504751
|View full text |Cite
|
Sign up to set email alerts
|

A measurement-based study of MultiPath TCP performance over wireless networks

Abstract: With the popularity of mobile devices and the pervasive use of cellular technology, there is widespread interest in hybrid networks and on how to achieve robustness and good performance from them. As most smart phones and mobile devices are equipped with dual interfaces (WiFi and 3G/4G), a promising approach is through the use of multi-path TCP, which leverages path diversity to improve performance and provide robust data transfers. In this paper we explore the performance of multi-path TCP in the wild, focusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
129
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 263 publications
(135 citation statements)
references
References 32 publications
6
129
0
Order By: Relevance
“…For MPTCP, a closely related research work is [72], which measures MPTCP performance with the aim to understand the benefit of using two interfaces with MPTCP over using either one of the interface with TCP. This study also focuses on the impact that flow size has on the average latency, and provides insights into the effect of path characteristic diversity on application level performance.…”
Section: Related Workmentioning
confidence: 99%
“…For MPTCP, a closely related research work is [72], which measures MPTCP performance with the aim to understand the benefit of using two interfaces with MPTCP over using either one of the interface with TCP. This study also focuses on the impact that flow size has on the average latency, and provides insights into the effect of path characteristic diversity on application level performance.…”
Section: Related Workmentioning
confidence: 99%
“…It compares various file transfer scenarios. [IMC13b] observes that 4-path MPTCP outperforms 2-path MPTCP, especially for larger files. However, for three congestion-control algorithms (LIA, OLIA, and Reno --see Section 3.2), there is no significant performance difference for file sizes smaller than 4 MB.…”
Section: Cellular/wifi Offloadmentioning
confidence: 82%
“…Another study of the performance of Multipath TCP in wireless networks was reported in [IMC13b]. This study uses laptops connected to various cellular ISPs and WiFi hotspots.…”
Section: Cellular/wifi Offloadmentioning
confidence: 99%
“…Flow control provides another limitation to the sending rate. Many external factors further influence the performance of MPTCP [20,4,19,6]. Especially the network's characteristics in terms of capacity, propagation delay, etc.…”
Section: Introductionmentioning
confidence: 99%